2016
DOI: 10.1021/jacs.6b03444
|View full text |Cite
|
Sign up to set email alerts
|

Distal Stereocontrol Using Guanidinylated Peptides as Multifunctional Ligands: Desymmetrization of Diarylmethanes via Ullman Cross-Coupling

Abstract: We report the development of a new class of guanidine-containing peptides as multifunctional ligands for transition-metal catalysis and its application in the remote desymmetrization of diarylmethanes via copper-catalyzed Ullman cross-coupling. Through design of these peptides, high levels of enantioinduction and good isolated yields were achieved in the long-range asymmetric cross-coupling (up to 93:7 er and 76% yield) between aryl bromides and malonates. Our mechanistic studies suggest that distal stereocont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 56 publications
(42 reference statements)
2
41
0
Order By: Relevance
“…These studies were driven by hypotheses that built on earlier observations in the catalysis of C–C bond forming cross-coupling reactions. As shown in Figure 2, our thinking about the attributes of guanidinylated peptides in Cu-catalyzed cross-coupling builds upon models wherein the nature of the C -terminus of the peptide proved critical for ensuring communication between the catalyst and substrate through a distal interaction with the remote arene ring and a cationic species such as Cs + or K + 11 . Given the new reaction media for the enantio-selective C–O bond formation, we speculated that the peptide ligands could adopt different secondary structures that effect the distal cation-π interaction and, ultimately, enantioselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were driven by hypotheses that built on earlier observations in the catalysis of C–C bond forming cross-coupling reactions. As shown in Figure 2, our thinking about the attributes of guanidinylated peptides in Cu-catalyzed cross-coupling builds upon models wherein the nature of the C -terminus of the peptide proved critical for ensuring communication between the catalyst and substrate through a distal interaction with the remote arene ring and a cationic species such as Cs + or K + 11 . Given the new reaction media for the enantio-selective C–O bond formation, we speculated that the peptide ligands could adopt different secondary structures that effect the distal cation-π interaction and, ultimately, enantioselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the organocatalytic acylation of diarylmethinyl bis(phenol) 1 shown in Figure 1b, 5 we recently showed that desymmetrization of 3 was possible through copper-catalyzed cross-coupling of malonyl nucleophiles when guanidinylated peptides such as L1 are used as ligands (eq 2). 11 As we show below, exploration of the complementary C–O bond forming desymmetrization reveals a surprising generality of the guanidinylated peptide ligands. Notably, this class of ligand had not been reported for transition metal catalysis prior to our initial study.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, peptides are chiral and this confers metallopeptides with the potential ability of mediating stereoselective transformations. 8, 9,10,11,12 Traditional oxidants offer little selectivity in reactions of non-functionalized organic substrates, which remain, collectively, a great challenge in organic chemistry. Novel metallopeptide catalysts, by virtue of these discussed features, can offer effective solutions to this challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Thef ield of asymmetric synthesis deals with these situations,o ften masterfully,t hrough the application of chiral catalysts, [3] which can take the form of transition-metal complexes, [4] small organic molecules, [5] enzymes, [6] or combinations of am etal-based catalyst and an organocatalyst. [11] We targeted ad esymmetrization process that would create ar emote stereogenic center on the nominally privileged diarylmethine scaffold (Figure 1d). [8] Fore xample,w hen am olecule possesses both as tereogenic center (Figure 1a)a nd an axis of chirality (Figure 1b), four possible diastereomers exist (Figure 1c)i namanner rendering asymmetric synthesis of all possible stereoisomers quite complex.…”
mentioning
confidence: 99%
“…[7] Ap articularly intriguing situation emerges when the scaffold of interest bears two different types of stereogenic elements. [11] We targeted ad esymmetrization process that would create ar emote stereogenic center on the nominally privileged diarylmethine scaffold (Figure 1d). Therefore,d eveloping new approaches to address all of these issues not only contributes to answering fundamental questions in the area of asymmetric catalysis,b ut also creates avenues for the consideration of novel chemotypes in medicinal chemistry.…”
mentioning
confidence: 99%